Ex-vivo characterization of regulatory T cells in pulmonary tuberculosis patients, latently infected persons, and healthy endemic controls. (September 2016) - Zewdie, Martha; Howe, Rawleigh; Hoff, Søren T.; Doherty, T. Mark; Getachew, Nahom; Tarekegne, Azeb; Tessema, Bamlak; Yamuah, Lawrence; Aseffa, Abraham; Abebe, Markos
Summary: Background: Regulatory T cells (Treg) are an essential arm of adaptive immunity not only in tolerance and autoimmunity but also in infectious diseases. In Tuberculosis (TB), it has been suggested that the frequency of Tregs is higher in the blood of TB patients when compared to healthy controls with subsequent decline after treatment. However, with the discovery that FOXP3, the hallmark marker of Tregs, is not exclusive to Tregs and the lack of specific markers for Tregs, it has been a challenge to fully understand the role of Tregs in TB. Method: We isolated PBMC from smear positive TB patients (TB, N = 13) before and after treatment, latent TB infected participants (LTBI, N = 8), and healthy endemic controls (EC, N = 9) and evaluated the frequency of different populations of Tregs and expression of FOXP3 by flowcytometry using six markers. Results: The findings in this study showed that the association of Treg frequency with TB disease depends on the phenotypic markers used. While the frequency of CD4 + CD25 +/hi T cells was higher in TB patients compared to LTBI individuals, there was no difference in the frequency of CD4 + CD25 + FOXP3 + CD127 lo Treg among TB, LTBI, or EC. However, delineation of Tregs into active and naïve subsets revealed a significant increase in FOXP3 expression in active primed Tregs (CD4 + CD25 + FOXP3 + CD127 lo CD45RO + Ki-67 + ) of TB patients compared to LTBI and EC; and a significantly higher frequency of resting primed (CD45RO + Ki-67 − ) Treg in QuantiFERON negative EC compared to TB patients. After treatment completion, there was a significant decline in the frequency of active primed Treg, median (IQR) from 12.4% (9.5–21.9) of Tregs to 9.3% (7.0–12.2); P = 0.003 Wilcoxon signed rank test. We conclude that Treg subsets may be differentially regulated and expressed in TB disease, cure, and infection.